Controlled disassembly of peptide amphiphile fibres - Löwik, Dennis W. P. M.; Meijer, Joris T.; Minten, Inge J.; van Kalkeren, Henri; Heckenmüller, Lisa; Schulten, Ines; Sliepen, Kwinten; Smittenaar, Peter; van Hest, Jan C. M. (Journal of peptide science, 2008)
In this paper, the introduction of both a methionine residue and a nitrobenzyl derivative as a labile linker between the peptide part and the hydrophobic alkyl chain of a peptide amphiphile are presented. These modifications are shown not to inhibit the formation of structured assemblies that analogous peptide amphiphiles lacking the linkers are able to form. Moreover, the introduction of either labile linker allows removal of the peptide amphiphile's stabilizing hydrophobic moieties to initiate a controlled disassembly of fibre aggregates. This is achieved by either treatment with CNBr or UV irradiation, respectively. These disassembly mechanisms could be the starting point for methodology that allows further manipulation of self‐assembled peptide amphiphile architectures. Copyright © 2007 European Peptide Society and John Wiley & Sons, Ltd.